Upaya Bersama Meningkatkan Kapasitas Sumber Daya Manusia dengan Pemahaman Literasi Hukum - Nugroho, Arief Teguh; Tarina, Arum; Prawitasari, Nining Yurista (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Capacity building of human resources through legal literacy understanding in Muktiwari Village aims to provide insights and comprehension in the areas of law and human rights, population administration, and protection of children and women from domestic violence. The legal education provided is expected to enhance legal literacy. The target audience for this activity is approximately 40 members of the Muktiwari Village community. The method used will be through lectures, case examples, and interactive Q&A sessions. Participants in this Community Service activity can benefit by gaining knowledge about (1) human rights as residents of Indonesia, a country governed by the rule of law, (2) the procedures and importance of handling and possessing documentation related to population administration in social and economic life, and (3) being aware of and understanding the actions to be taken by women and children experiencing domestic violence.